Stiffness Optimal Modulation of a Variable Stiffness Energy Storage Hip Exoskeleton and Experiments on Its Assistance Effect - Bingshan Hu; Fengchen Liu; Ke Cheng; Wenming Chen; Xinying Shan; Hongliu Yu (IEEE, 2023)
Lower limb energy storage assisted exoskeletons realize walking assistance by using the energy stored by elastic elements during walking. Such exoskeletons are characterized by a small volume, light weight and low price. However, energy storage assisted exoskeletons adopt fixed stiffness joints typically, which cannot adapt to changes of the wearer’s height, weight, or walking speed. In this study, based on the analysis of the energy flow characteristics and stiffness change characteristics of lower limb joints during a human walking on flat ground, a novel variable stiffness energy storage assisted hip exoskeleton is designed, and a stiffness optimization modulation method is proposed to store most of the negative work done by the human hip joint when walking. Through the analysis of the surface electromyography signals of the rectus femoris and long head of the biceps femoris, it is found that the muscle fatigue of the rectus femoris is reduced by 8.5% under the optimal stiffness assistance condition, and the exoskeleton provides better assistance under the optimal stiffness assistance condition.